TPACK Based: A Need Analysis for ELT Materials Development - Devi, Ravena; Ikhsanudin, Ikhsanudin (Elsya : Journal of English Language Studies, 2023)
Maintaining current levels of knowledge necessitates putting learning into daily life. Currently, the development of technology and information has been very rapid, so it is possible to carry out technology-based learning. The term "TPACK" refers to the integration of conceptual frameworks related to technology, pedagogy, and content knowledge. The aim of this study was to determine if one of Kalimantan Barat schools was prepared to use TPACK in its teaching methodology. Descriptive analysis is the research method that is implemented. The techniques used to collect the data are observation of the school's infrastructure and amenities, interviews with a number of students and one of the English teachers, and student questionnaire responses. The findings revealed that the school and teachers were not prepared to include TPACK in learning and teaching activities. Even though the students were prepared enough for TPACK-based teaching and learning, it could be difficult because the school and teachers were not prepared. The observation reveals a scarcity of learning resources. The interview findings revealed that there are impediments to the use of TPACK in teaching and learning activities, such as a lack of technological skills, difficulty adapting to existing technology, and student indiscipline while utilizing technology in learning activities. Based on the study's findings, it is possible to conclude that certain demands must still be satisfied in order to accomplish TPACK-based learning.